Black Skin White Mask: Hybrid Identity of the Main Character as Depicted in Tagore's The Home and The World - Yanggi Mertania; Dina Amelia (Linguistics and Literature Students' Journal, 2020)
This research paper describes the analysis of a literary work entitled The Home and The World by Rabindranath Tagore. This novel illustrates Tagore’s inner battle about his ideas on the Western culture and on the revolution against Western culture when India was colonized by the British. These ideas portrayed in one of the main characters, Nikhil. Tagore represents himself as Nikhil, the hybrid, who is positioned between British and Indian cultures. The main purpose of this research is to describe the hybrid identity of Nikhil as one of the main characters in the novel within the context of colonized society and the Swadeshi movement. This research applied the post-colonial approach and hybrid identity theory by Homi. K. Bhabha and also applied the descriptive qualitative method to depict the problem by using the words. Library research was applied in the context of the data collecting process. The data are dialogues and narrations about the hybrid identity of Nikhil in The Home and The World novel. Based on the research conducted, it was concluded that the impact of British colonialism led to the formation of a hybrid identity process in Indian society. First, there was a hybrid identity of Nikhil as a part of the colonized society in education, lifestyle, culture, and social aspects. The second was the hybrid identity of Nikhil in the Swadeshi movement.Keywords: Black skin white mask, colonialism, hybrid identity, post-colonial, rabindranath tagore, swadeshi movement, the home, and the world.